2020
DOI: 10.1111/nmo.13812
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture of different treatment frequency in postprandial distress syndrome: A pilot randomized clinical trial

Abstract: Background The evidence for different frequencies of acupuncture treatment in postprandial distress syndrome (PDS) is insufficient. This study determined whether 3 sessions per week of acupuncture treatment are superior to 1 session per week for symptomatic outcomes in PDS. Methods This 16‐week randomized clinical pilot trial was conducted in an outpatient setting in China. Patients with PDS were randomly assigned to receive 3 sessions per week of acupuncture (group H) or 1 session per week of acupuncture (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
(64 reference statements)
0
20
0
Order By: Relevance
“…The Cochrane Database Systematic Review in 2014 found that acupuncture had some efficacy as a treatment for FD, but the evidence level of the clinical studies in the review was mostly low (Table 3) [83]. However, in 2020, a randomized, controlled trial in over 200 patients with FD found that acupuncture showed therapeutic efficacy compared with sham acupuncture [84]. Although acupuncture and moxibustion are both widely practiced in Japan, no clinical studies with a high evidence level of either of them as a treatment for FD have been reported from Japan.…”
Section: Future Research Themesmentioning
confidence: 99%
“…The Cochrane Database Systematic Review in 2014 found that acupuncture had some efficacy as a treatment for FD, but the evidence level of the clinical studies in the review was mostly low (Table 3) [83]. However, in 2020, a randomized, controlled trial in over 200 patients with FD found that acupuncture showed therapeutic efficacy compared with sham acupuncture [84]. Although acupuncture and moxibustion are both widely practiced in Japan, no clinical studies with a high evidence level of either of them as a treatment for FD have been reported from Japan.…”
Section: Future Research Themesmentioning
confidence: 99%
“…However, the negative results in four of these trials were 57% and thus higher than the positive results, which indicated that the efficacy of acupuncture remained controversial. According to the ICD-11, categories of disease systems among registration of acupuncture trials included the musculoskeletal system and connective tissue disorders (218), the nervous system (110), the genitourinary system (110), signs, symptoms, and clinical findings (94), the digestive system (84), mental, behavioral, and neurodevelopmental disorders (80), pain (67), neoplasms (58), the circulatory system (39) endocrine, nutritional, and metabolic diseases (38), pregnancy, childbirth and puerperium (34), sleep-wake disorders (31), the respiratory system (26), injury, poisoning and certain other consequences of external causes (18), the skin ( 17), the visual system ( 16), the immune system ( 14), certain conditions originating in the perinatal period (6), certain infectious or parasitic diseases (5), the blood and bloodforming organs (4), the ear and mastoid process (4), factors influencing health status or contact with health services (3), and conditions related to sexual health (1).…”
Section: Publications From the High-quality Clinical Trialsmentioning
confidence: 99%
“…It has also become popular in treating infantile colic and has shown effects on in vitro fertilization and veterinary care. In recent years, acupuncture treatment for non-painful conditions has been increasing, such as chemotherapy-induced nausea and vomiting [16] , peripheral neuropathy [17][18] , radiotherapy-induced dysphagia [19] , xerostomia [20] , hot flashes in breast cancer [21] , dyspnea from lung cancer [22] , cancer-related fatigue [23] and other cancer-related symptoms, urinary incontinence [24] , postmenopausal dry eye syndrome [25] , and digestive systemrelated conditions such as postprandial distress syndrome [26] , and chronic severe functional constipation [27] . Acupuncture clinical research has generated high-quality evidence in the treatment of these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al at the Beijing University of Chinese Medicine recently performed a pilot randomized clinical trial to show the superiority of three sessions per week versus one session per week of acupuncture for symptomatic relief of FD, especially PDS. 87 They showed that, after 4 weeks, the complete elimination rate of core symptoms was 26.7% (95% CI 12.3%-45.9%) for three sessions/week (H) and 10.0% (95% CI 2.1%-26.5%) for one session/week (L) (P =0.095) and that there were significant differences between the H and L groups at weeks 8, 12, and 16 (P = 0.038, 0.02, and 0.02). Although they have obtained data from high-quality clinical trials, this result is still preliminary; a multicenter RCT of acupuncture for PDS with a larger sample is necessary to validate these results.…”
Section: Acupuncture For Fdmentioning
confidence: 99%